Making Hospital Governance Healthier for Nurses - Kim Clark; Shelley Beatty (ACHSM, 2016)
The current research examined front line nurse expectations of non-metropolitan public hospital governance. In doing so, it explored the relevance of two dominant, competing Agency and Stewardship governance theories to these organisations. Two studies were conducted with the first establishing an inventory of notional nurse preferences for governance and the second testing these with a random sample of front-line non-metropolitan hospital nurses across one Australian State, with the aim of identifying valid and reliable measures. The study data suggest nurses working in nonmetropolitan public hospitals expect governance practices to reflect: respect for and engagement with clinical perspectives; utilisation of evidence-based planning; and effective engagement with local communities. Scales with good consistency and criterion and construct validity measuring these three components were identified. The study provides evidence that nurses expect and value a style of hospital governance that is consistent with Stewardship Theory. The results also suggest that governance is an important enough issue for nurses that it significantly affects their turnover intentions. This has important implications for healthcare leaders concerned about the sustainability of public hospitals. Abbreviations: NPM - New Public Management; PCA - Principal Components Analysis.